Varicocele Surgery Improves Sperm Count in Infertile Oligospermic Patients and so Improves Fertility; A Study in a Tertiary Care Hospital - Jamaluddin M.; Abbas Hussain SM; Ayesha AK; Hina RS (Faculty of Medicine, UKM Medical Centre, 2015)
The objective of this study was to find out the role of varicocele surgery in oligospermic infertile patients. It was a prospective and descriptive study carried out in Surgical Unit-I, Abbasi Shaheed Hospital and Karachi Medical and Dental College (KMDC), Karachi from April 2004 to March 2014. In this study, all patients of infertility due to low sperm count having bilateral varicocele were included while those patients having azoospermia or patients with unilateral varicocele were excluded. All patients were clinically assessed for bilateral varicocele and confirmed by ultrasonography of scrotum and relevant investigations were done. Patients were prepared for varicocele surgery and ligation of pampiniform plexus done. Semenanalysis were done during follow up and results were analyzed on SPSS version 14. Total fifty seven patients (n=57) were included in which age range was 20 to 30 years in 33.3%, 31 to 40 years in 42.1%, 41 to 50 years in 19.3% and 51 years to onwards in 05.3% patients only. Chronic smoking was found in 68.4% patients while 31.6% were nonsmokers. Normal testes was found in 77.19% while 22.81% had smaller (atrophied) testes. Very low sperm count was in 15.79%, 50.88% had low sperm count and 33.33% had near normal sperm count. All patients were operated for bilateral varicocele and discharged. Follow-up semen analysis showed improvement and semen analysis became normal in 19.3% after six months, 21.05% after nine months and 36.84% after one year of surgery while 22.81% had no improvement even after one year of surgery. Thus, patients with bilateral varicocele having low sperm count showed improvement in sperm count after varicocele surgery and so infertile patients may become fertile after varicocele surgery.